NUTRIENT CONTENT, PROTEIN DIGESTIBILITY, AND ACCEPTABILITY OF SUBSTITUTING TEMPEH GEMBUS NUGGETS WITH TILAPIA FISH - Ina Susanti; Diana Nur Afifah; Hartanti Sandi Wijayanti; Ninik Rustanti (Media Gizi Indonesia, 2021)
Nuggets are protein rich food that is widely; consumed in Indonesia because of its good taste and easy preparation. The substitution of tilapia fi sh in tempeh gembus nugget act as a healthy alternative composition which contain high protein, fi ber, but low in fat. Therefore, this research was aimed to determine the eff ect of substitution of tilapia fi sh on the nutrient content, protein digestibility, and acceptability of tempeh gembus nuggets to obtain a formulation in accordance with the Daily Value (DV) 2150 kcal. A randomized experimental study was carried out on tilapia fi sh in substitution of 0%, 20%, 40%, 80%, and 100%. The protein, fat, carbohydrate, water, ash, and dietary fi ber content analysis were determined using the Kjeldahl, Soxhlet, carbohydrate diff erence, gravimetric, dry ash, and enzymatic-gravimetric methods. Furthermore, the protein digestibility was conducted by in vitro method, while the organoleptic tests were determined using hedonic tests. The organoleptic data was statistically analysed using ANOVA and Friedman tests. The substitution of tilapia fi sh increased the content of protein, water, and dietary fi ber while decreasing fat, carbohydrates, ash, and protein digestibility. The most preferred tempeh gembus nugget formulation by panelists was 80% substitution treatment of tilapia fi sh. In conclusion, the recommended formulations are the substitution of 40% and 80% of tilapia fi sh considering the nutrient content, protein digestibility and acceptability.